Traditional ethnobotanical knowledge of important local plants in Sudhnoti, Azad Kashmir, Pakistan - Muhammad Ishtiaq; Tauqeer Sardar; Iqbal Hussain; Mehwish Maqbool; Muhammad Waqas Mazhar; Abida Parveen; Muhammad Ajaib; Khizar Hayat Bhatti; Tanveer Hussain; Alia Gul; Muhammad Azeem; Humaira Khanum; et al. (Scientific Reports)
Abstract This research purpose was focused to document the traditional ethnobotanical knowledge (TEK) associated with important wild plants and indigenous communities residing in mountainous zone of District Sudhnoti of Azad Jammu and Kashmir, Pakistan and to determine their conservation status with suggestions and recommendations to protect and propagate the rare and endangered wild flora of the area for sustainable use. The data regarding traditional ethnomedicines (TEMs) and phytogeography with conservation analysis of wild plants were collected via structured and semi structured interviews of 150 participants belonging to various professions and of both genders. Prior consent and permission were obtained from family heads and from all the participants, and the data were shared with all the informants through the local female translator guide. To validate the collected data, various microstatistical tools, such as the informant consensus factor (ICF), fidelity level (FL) and data matrix ranking (DMR) were used. The relative frequency of citations (RFC) and rank order of popularity (ROP) were also calculated to determine and authenticate the relative importance of TEMs which may be further studied in future research and used for drug discovery. In the present study, 150 locally important plants belonging to 69 families were documented, and the Rosaceae was the most dominant and prevalent family. The results indicated that many locally important plants have multiple uses such as food, medicine, fodder, shelter, ornamental and fuel. The TEMs obtained from these plants have been known to be useful for curing various infirmities such as flu, renal disorders, fever, malaria, cough, migraine, whooping cough, influenza, skin rashes, allergies, stomach aches, wounds and bruises, diabetes, tumours and joint pains. The ICF analysis revealed that renal calculus, malaria, fever, whooping cough, rheumatoid arthritis and arthritis were prevalent infirmities of the mountainous area. The FL analysis indicated the popularity of these plants used in various TEMs and among these Artemisia maritima and Berberis lycium were the most common. The DMR indicated that Pinus roxburghii was the most common species being used for multipurpose by the indigenous communities. The highest use value index was found for Indigofera linifolia. The relative frequency of citations was calculated to determine the importance of plants in traditional ethnomedicine, highlighting Morus nigra, Pinus wallichiana, and Rosa indica as significant species. The Jaccard index indicated a high level of novelty in the research which can be exploited for neo-drug discovery and drug development. In conclusion, this study has successfully documented the ethnobotanically and ethnomedicinally important plants in District Sudhnoti, Azad Jammu and Kashmir, Pakistan. The findings of this research contribute to the preservation and documentation of cultural heritage, as well as provide a foundation for further studies in ethnobotany, ethnopharmacology and biodiversity conservation efforts for sustainable provision of wild flora to the indigenous communities which will also assist in combating drasting climatic changes.